The Influence of Job Satisfaction, Work Motivation, and Work Environment on Employee Morale at the Medan City Market Regional Public Company - John Kerli; Muhammad Nabil Arya; Salman Faris; Nasib Nasib (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the effect of job satisfaction, work motivation, and work environment on employee morale at Medan City Market Regional Public Company. The population consisted of 418 employees, and a sample of 82 respondents. A quantitative approach was employed, with data collected through Likert-scale questionnaires. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that job satisfaction, work motivation, and work environment have a positive and significant effect on employee morale, both partially and simultaneously. The coefficient of determination (Adjusted R²) is 0.863, indicating that 86.3% of the variance in employee morale is explained by these variables, while the remaining 13.7% is influenced by other factors not examined in this study. These results highlight the importance of improving job satisfaction, strengthening work motivation, and creating a supportive work environment to enhance employee morale.